Males’ Lived Experience with Self-Perceived Pornography Addiction: A Qualitative Study of Problematic Porn Use - Hanseder, S.; Dantas, Jaya A R (MDPI, 2023)
The positive impact of pornography use has been demonstrated; however, most research points towards problematic, compulsive, or excessive engagement with pornography and associated adverse effects on well-being. However, results remain inconclusive and qualitative research capturing perspectives of affected people is scarce. This phenomenological study aimed to explore the perspective and lived experience of males with a self-reported addiction to pornography. Semi-structured in-depth interviews with 13 males aged between 21 and 66 years from Australia and the USA were conducted. A thematic analysis of the transcripts was undertaken, resulting in the identification of four themes. The interviews explored the participants’ reasoning for determining themselves as porn addicts, investigated patterns of use, examined the perceived multifaceted impacts of pornography use, illustrated applied individual strategies to overcome the addiction, and proposed interventions helping to inform future recommendations. Experiences and perceptions of pornography addiction were consistently depicted as problematic and harmful. Most participants described an inability to stop their consumption despite experiencing adverse effects. Commonly reported was a gradual increase in the use of and consumption of new or more shocking content. Consumption of content was outlined as an escape or coping mechanism for negative emotions or boredom. Participants reported a variety of applied strategies to manage their addiction and suggested recommendations. Investigation into strategies for the identification of problematic pornography use, its conceptualization, associated health outcomes, and effective preventative and interventional strategies are required to provide academic consistency, support those negatively affected by pornography, and achieve increased public awareness of the issue.